2023
DOI: 10.21037/qims-22-1219
|View full text |Cite
|
Sign up to set email alerts
|

Current status and trends in quantitative MRI study of intervertebral disc degeneration: a bibliometric and clinical study analysis

Abstract: Background: Quantitative magnetic resonance imaging (MRI) has the function of noninvasive quantitative evaluation, providing unique advantages in intervertebral disc degeneration (IDD) assessment. Although studies exploring the field for domestic and international scholars are increasingly being published, there is a lack of systematic scientific measurement and clinical analysis of the literature in this field.Methods: Articles published from the respective database establishment to September 30, 2022, were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Figure 8 presents a dual-map visualization of the co-citation networks, with citing journals on the left and cited journals on the right, and the colored lines representing citation pathways. [26][27][28] The figure reveals three main citation paths, indicating that papers published in neurology/sports/ophthalmology journals typically cite articles from health/nursing/medicine, sports/rehabilitation/sport, and psychology/education/social journals. Based on the aforementioned journal analysis, scholars can derive some valuable insights.…”
Section: Analysis Of Journalsmentioning
confidence: 99%
“…Figure 8 presents a dual-map visualization of the co-citation networks, with citing journals on the left and cited journals on the right, and the colored lines representing citation pathways. [26][27][28] The figure reveals three main citation paths, indicating that papers published in neurology/sports/ophthalmology journals typically cite articles from health/nursing/medicine, sports/rehabilitation/sport, and psychology/education/social journals. Based on the aforementioned journal analysis, scholars can derive some valuable insights.…”
Section: Analysis Of Journalsmentioning
confidence: 99%
“…To a significant extent, highly cited publications can reflect the main research themes and knowledge structure of a given field, and are considered to be high-quality research with significant academic influence. [94][95][96] Among them, the most cited publication is a study by Wilke et al published in Spine in 1999, which measured intradiscal pressure in a volunteer and found that sitting may actually result in lower intradiscal pressure than standing, and that muscle activity increases pressure. The study also emphasized the importance of continuously changing positions to promote fluid (nutrient) flow to the disc, and suggested that some of the physical therapy methods studied may need to be reevaluated.…”
mentioning
confidence: 99%